The Development of Business Intellectual Competency for Modern Thai SMEs Towards Business Performance in Thailand 4.0 Era - Phungphol, Wilai; Jadesadalug, Viroj; Sansook, Jantana (Dusit Thani College Journal, 2020)
The objectives of this research were to 1) Study the roles, concepts, and experiences of modern entrepreneurs in business intellectual competency that affect entrepreneurs in the Thailand 4.0 era. 2) Study practical work based on the successful experiences of the entrepreneurs’ development model in the category of manufacturing, service, wholesaling and retailing, and 3) Build in-depth guidelines towards business performance. The study was in the postmodernism uses qualitative method in explaining and analyzing the most benefits. Therefore, the purposive selection was determined the criteria for considering the main data, totaling 14 key informants. The research tool was a document analysis. In-depth interviews by using the phenomenological approach was a successful guideline and lesson in the business management of key informants expressed by the narrative approach. The results show that business intellectual competency built into business owners of all ages. It consists of the following priorities: 1) Innovative competence. 2) Potential change leaders, team building, and freedom to think and operate. 3) Effective network construction with negotiation skills. 4) Creative risk management and 5) Ethical proactive business potential In which the business intellectual competency of modern Thai SMEs affects the success of the organization innovation management. Creative marketing effectiveness and business results, besides, the aspects of 1) A strong commitment to the business, and 2) Social characteristics in business operations have an impact on the business intellectual performance. The practical experience in the study found guidelines to prepare the model for the development of the business intellectual competency of modern Thai SMEs through creating organizational culture strategies. Continuous action to achieve the goal and business owners who have to start developing themselves in the role model. The guidelines for the development of modern Thai SMEs are beneficial for academic and management towards Thailand 4.0 under the principles of C-O-G-N-I-T-I-V-E. They mean C-Courageous change into new things, O-Optimistic at things around positively, G-Good Governed on transparent ethics, N-Noticeable think for business, I-Innovative difference, T-Technology-Driven for modern technology, T-Initiative leader of thoughtfulness, V-Visual concrete foresight, and E-Enthusiastic sharing.